ANALYSIS OF FACTORS THAT INFLUENCE THE INTENTION AND BEHAVIOR OF FOOD AND BEVERAGE MSMES IN CARRYING OUT HALAL CERTIFICATION - Ricky Widiarto; Indra Indra (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of halal literacy and awareness, religiosity, perceived benefits, perceived ease, and external support on the intention and actual behavior of Micro, Small, and Medium Enterprises (MSMEs) in obtaining halal certification. The research focuses on identifying the most consistent factors affecting both variables to provide strategic recommendations for accelerating halal certification adoption among MSMEs. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through a survey of 102 MSME owners in the food and beverage sector located in Bogor City and Bogor Regency, all of whom had already obtained halal certification. Respondents were selected based on the criteria of holding halal certification and domicile in the study area. The findings reveal that perceived ease is the most consistent factor influencing both the intention and actual behavior of MSMEs in obtaining halal certification, showing significant effects on both variables. External support significantly affects intention at the 10% significance level, while intention itself is a direct determinant of actual behavior. In contrast, halal literacy and awareness, religiosity, perceived benefits, and external support toward actual behavior show no significant influence. These results indicate that, although knowledge and religious values are conceptually important, they are insufficient to drive actual behavior without a perceived ease in the certification process. This highlights the need for strategies that focus on simplifying procedures, increasing access to practical information, and strengthening external support to convert intention into actual action.